The economic Loss of Hypertention Sufferers Patient With Accompanying Diseases At Inpatient Unit of Anutapura General Hospital - Syafiqah, Syafiqah (Tadulako University, 2019)
Hypertension is one of the major problems in Indonesia and in the world. The number of hypertensive cases in Palu city in 2015-2017 was increased. In 2015 as many as 8407 cases, the year 2016 as many as 8697 cases and 2017 as many as 9406 cases. This research aims to determine the economic loss that is borne by hypertension sufferers with concomitant diseases in the inpatient unit of RSU Anutapura Palu. This type of research is quantitative descriptive. Research was conducted from March to June 2019. The population is all patients suffering from hypertension with a concomitant illness that conducts hospitalisation in RSU Anutapura Palu, the number of samples of 78 patients. Primary data collection is through questionnaires and secondary data through the study of patient record documents and other supporting documents. Total economic loss for people with hypertension with concomitant illness in inpatient unit of RSU Anutapura Palu amounting to Rp. 234.318.617 with an average of Rp 3.004.084 per sufferer. The results of this study also showed that the magnitude of the losses suffered by patients especially in patients who are still productive work is advised to carry out regular control every month to prevent the expenditure of the cost of illness that will continue Increased.